PENGARUH PEMBERIAN DETERJEN TERHADAP MORTALITAS IKAN PLATY SP. - KAMISWARI, RIZKY (Universitas Negeri Surabaya, 2013)
One of the causes of water pollution are domestic wastes in the form of residual detergent. In the waste surfactants contain chemicals that are more resistant and does not change in a variety of media. Antiseptic ingredient in soap or detergent can disrupt the microorganisms, which is in the nature of water can be dangerous. This study aimed to determine the effect of detergent on Platy Sp. fish mortality at doses of 0 ppm, 18 ppm, 36 ppm, and 54 ppm of deterjent for 4 days treatment. The method used in this study was experimental design. The result of mortality obtained were analyzed using descriptive analysis. From the research it could be concluded that the concentration of detergent affect the rate of mortality in Platy Sp. fish positively. At 18 ppm detergent was the mortality of Platy Sp. longer than the mortality of the concentration at 54 ppm detergent.